Anaphylactoid reactions induced by Shuanghuanglian injection and Shenmai injection and metabolomics analysis - Zhang, Chi; Ouyang, Linqi; Zhang, Xili; Wen, Wen; Xu, Yuqin; Li, Shan; Li, Yingyu; He, Fuyuan; Liu, Wenlong; Liu, Hongyu (Frontiers in Pharmacology, 2023)
Shuanghuanglian injection (lyophilized) (SHLI) and Shenmai injection are two commonly used traditional Chinese medicine injections (TCMI). SHLI is commonly used to treat respiratory tract infection. SMI is mainly used to treat cardiovascular diseases. Despite their widespread clinical use, anaphylactoid reactions (ARs) induced by SHLI and SMI have been reported, which have attracted broad attention. However, the impact of ARs on metabolic changes and the underlying mechanisms are still unclear. Here, we investigated the anaphylactoid reactions induced by SHLI and SMI, as well as their potential mechanism. ICR mice were used as model animals and were treated with normal saline, C48/80, SHLI and SMI, respectively. The behavior of mice, auricle blue staining and Evans Blue exudation were used as indexes to evaluate the sensitization of SHLI and SMI and determine the optimal sensitization dose. Anaphylactoid mice model was established based on the optimal dose and enzyme-linked immunosorbent assay (ELISA) was used to model verification. Afterwards, plasma samples of administered mice were profiled by LC-MS metabolomics and analyzed to evaluate the changes in metabolites. We found that high doses of both SHLI and SMI can induce severe anaphylactoid reactions while the reaction induced by SMI was weaker. A Partial Least-Squares Discriminant Analysis (PLS-DA) score plot indicated that following administration, significant metabolic changes occurred in mice. We identified 23 distinct metaboli tes in SHLI groups and 11 in SMI groups. Meanwhile, different metabolic pathways of SHLI and SMI were predicted by different metabolites. Study showed that both SHLI and SMI can induce varying degrees of anaphylactoid reactions, a positive correlation between response intensity and dose was observed. However, its mechanism requires further verification. Deleted: Traditional Chinese medicine injection (TCMI) has better 37 efficacy in clinical application 38 Deleted: , but its adverse reactions seriously hinder the further 39 development.